PENGARUH MOTIVASI, PENDIDIKAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. BAROKAH NURA SEKAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Sonnyalia, Astrid Bellinda; Sari, Lita Permata; Fandiyanto, Randika (Fakultas Ekonomi dan Bisnis, 2024)
The aim of this research is to analyze the influence of variablesThe Impact of Educational Motivation and Competence on Employee Performance at PT. Baokah Nura Sekawan with Job Satisfaction as an Intervening Variable. By using the Partial Least Square (PLS) Structural equation model. Results of direct influence hypothesis testing using the Smart PLS 3.0 application. Motivation has a significant positive effect on job satisfaction, Education has a positive but not significant effect on job satisfaction, Compensation has a positive but not significant effect on job satisfaction, Motivation has a positive but not significant effect on employee performance, Education has a significant positive effect on employee performance, Compensation has a positive but not significant effect on employee performance, Job satisfaction has a significant positive effect on employee performance, Motivation has a positive but not significant effect on Employee performance through job satisfaction, education has a positive but not significant effect on employee performance through job satisfaction, and compensation has a positive but not significant effect on employee performance through job satisfaction.